Construct validity of Croatian version of the Pavlovian Temperament Survey (PTS) - Tatalović Vorkapić, Sanja (Array, 2012)
The aim of this study was to examine the construct validity of Pavlovian Temperament Survey (PTS) by determining the relationship between three Strelau´s dimensions of temperament (strength of excitation, strength of inhibition, mobility) and basic dimensions of personality as were defined by Eysenck and in the five-factor model of personality. It was expected that strength of excitation and mobility would have significant positive correlations with extraversion and negative correlations with neuroticism, while strength of inhibition would show significant negative correlations with neuroticism. Within two studies (N1 = 74 female students, Mage = 22 ; N2 = 54 female students, Mage = 20), Croatian version of PTS, Five−Factor Nonverbal Personality Questionnaire FF−NPQ, and Eysenck’s Personality Questionnaire EPQ R/A were used. The reliability coefficients for all three instruments were satisfactory, although not very high. Coefficients of correlation determined in the first study were not entirely in agreement with either theoretical expectations or empirical results of other authors, probably due to small sample size. However, the results of the second study were in accord with the expected pattern of significant correlations and that could be considered an indicator of good construct validity of PTS. Since this was a preliminary study the results provide only a general insight into the research aim, and represent a good starting point for future validation studies of the Croatian version of PTS.